Metformin Regulates Alveolar Macrophage Polarization to Protect Against Acute Lung Injury in Rats Caused by Paraquat Poisoning - Yuan, Ding; Li, Yi; Hou, Linlin; Yang, Fang; Meng, Cuicui; Yu, Yanwu; Sun, Changhua; Duan, Guoyu; Xu, Zhigao; Zhu, Guiying; Guo, Jianjun; Zhang, Leilei; et al. (Frontiers in Pharmacology, 2022)
This study explored the role of metformin (MET) in regulating the polarization of alveolar macrophages to protect against acute lung injury (ALI) in rats caused by paraquat (PQ) poisoning. The in vivo studies showed that the 35 mg/kg dose of MET increased the survival rate of rats, alleviated pathological damages to the lungs and their systemic inflammation, promoted the reduction of the pro-inflammatory factors interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) levels, and increased the anti-inflammatory factor IL-10 levels in the rat serum. At the same time, the MET intervention decreased the expression of M1 macrophage marker iNOS in the lungs of the PQ-poisoned rats while increasing the M2 macrophage marker, Arg1, expression. In vitro, the concentration of MET >10 mmol/L affected NR8383 viability adversely and was concentration-dependent; however, no adverse impact on NR8383 viability was observed at MET ≤10 mmol/L concentration, resisting the reducing effect of PQ on NR8383 vitality. The PQ-induced NR8383 model with MET intervention showed significantly reduced secretions of IL-6 and TNF-α in NR8383, and lowered expressions of M1 macrophage markers iNOS and CD86. Additionally, MET increased IL-10 secretion and the M2 macrophage markers, Arg1 and Mrcl, expressions. Therefore, we speculate that MET could regulate alveolar macrophage polarization to protect against PQ-poisoning caused ALI.